Correlation of the movements of the Severn Suspension Bridge derived with GNSS with temperature variations - Roberts, Gethin Wyn; Tang, X. (2016)
In March 2010, four days of GNSS data were gathered on the Severn Suspension Bridge. The GNSS antennas were located on the tops of the four support towers, as well as five locations on the suspension cables. The Severn Bridge has a main suspended span of 998m long. The GNSS data were gathered at rates of 10Hz and 20Hz between the 10th to the 12th and on the morning of the 18th March 2010. In addition to the GNSS data, the air and steel temperatures were gathered every 10 minutes. The GNSS data were processed in an On The Fly manner relative to a reference GNSS receiver located on a solid building adjacent to the Bridge.